Magnetic domain wall motion in SrRuO3 thin films. (February 2020) - Zahradník, Martin; Uhlířová, Klára; Maroutian, Thomas; Kurij, Georg; Agnus, Guillaume; Veis, Martin; Lecoeur, Philippe
Abstract: Influence of substrate miscut on magnetization dynamics in SrRuO3 (SRO) thin films was studied. Two films were grown on SrTiO3 substrates with high (∼ 1°) and low (∼ 0.1°) miscut angles, respectively. As expected, high miscut angle leads to suppression of multi-variant growth. By means of SQUID magnetometry, comparable relaxation effects were observed in both the multi-variant and the nearly single-variant sample. Differences in the magnetization reversal process were revealed by magnetic force microscopy. It showed that the multi-variant growth leads to higher density of defects acting as pinning or nucleation sites for magnetic domains, which consequently results in deterioration of magnetic properties. It was demonstrated that the use of high miscut substrate is important for fabrication of high quality SRO thin films with low density of crystallographic defects and excellent magnetic properties. Graphical Abstract: Unlabelled Image Highlights: Spatially resolved dynamics of SrRuO3 magnetization was captured at low temperatures. Low-miscut angle (∼ 0.1°) of SrTiO3 substrate leads to increased density of domain nucleation and pinning centres in SrRuO3 films. Presence of anti-phase boundaries results in magnetic structures persisting up to high magnetic fields (∼ 14 T).